The Georgian Milieu and the Metaphrastic Menologion: Three Accounts about Symeon Metaphrastes (Interfaces: A Journal of Medieval European Literatures, 2022)
The article investigates the reception history of the Metaphrastic menologion in the medieval Georgian milieu. The Georgian literati were the first non-Greeks to translate the metaphrastic hagiographical literature. Soon after Symeon Metaphrastes (also called Symeon the Logothetes; end of tenth century) finished his literary project, the Georgian monks at the monastery of Iviron on Mount Athos started translating not only Symeon's saints' lives but also adopted metaphrastic method and applied it to other texts. The tradition set in motion at Iviron was successfully continued and cultivated by Georgians in various parts of the Byzantine Empire, mainly in Constantinople and at the Black Mountain near Antioch. The increased interest of the Georgian learned monks in Symeon Metaphrastes' saints' lives demonstrates the popularity of Metaphrastic menologion and success of Symeon's literary project. The article focuses on several extant Georgian sources that provide unique information about Symeon Metaphrastes, his project and rewriting method. The accounts by Ephrem Mc‘ire, Theophilos the Hieromonk, and Ioannes Xiphilinos the Younger that survive only in Georgian, shed new light on the history and trajectory of the metaphrastic movement. The accounts include manuscript colophons, commentaries, and prayers for the rulers. These testimonies allow one to understand why Georgians wholeheartedly embraced literary trends set in motion in the center of the Byzantine Empire.
Keywords: metaphrasis; hagiography; translation; Georgia; Symeon the Logothetes; Ephrem Mc‘ire; Theophilos the Hieromonk